How do you simplify 14sqrt20 - 3sqrt125?

2 Answers
Jul 2, 2016

14sqrt20-3sqrt125=13sqrt5

Explanation:

14sqrt20-3sqrt125

= 14sqrt(2xx2xx5)-3sqrt(5xx5xx5)

= 14sqrt(ul(2xx2)xx5)-3sqrt(ul(5xx5)xx5)

= 14xx2xxsqrt5-3xx5xxsqrt5

= 28sqrt5-15sqrt5

= (28-15)sqrt5

= 13sqrt5

Jul 2, 2016

14sqrt(20)-3sqrt(125) = 13sqrt(5)

Explanation:

Note that if a, b >= 0 then:

sqrt(ab) = sqrt(a)sqrt(b)

In particular:

sqrt(a^2b) = sqrt(a^2)sqrt(b) = asqrt(b)

So we can move square factors outside the square root like this:

14sqrt(20)-3sqrt(125)

=14sqrt(2^2*5)-3sqrt(5^2*5)

=14sqrt(2^2)sqrt(5)-3sqrt(5^2)sqrt(5)

=(14*2*sqrt(5))-(3*5*sqrt(5))

=28sqrt(5)-15sqrt(5)

=(28-15)sqrt(5)

=13sqrt(5)